Language Features of Men and Women in Tekotok Animated Videos - Niswatin Nurul Hidayati (UIN Raden Mas Said Surakarta, 2022)
The purpose of this research was to describe the language features of men and women in the animated video in the Tekotok Youtube Channel. In addition, to describe how the videos describe men and women. The research method used was qualitative research. The data source used in this study was speech from the figures in several animated videos from Youtube Channel Tekotok taken randomly. The results showed that based on the language features raised by the Lakoff, the majority was not in accordance with the speech mentioned by woman character where there were no Color Words, Empty Adjectives, Hedge, Intensifiers, Question Tags, and Emphatic Stress. Even some of the language features are contrary to what was delivered by Lakoff’s theory. For example, the Hypercorrect Grammar feature in this context is Indonesian not found. Likewise with the Super Polite Form, for example, there are several swear words of feed delivered by the woman character.